2017
DOI: 10.22438/jeb/38/5/mrn-340
|View full text |Cite
|
Sign up to set email alerts
|

Differences in seed vigour traits between desi (pigmented) and kabuli (non-pigmented) ecotypes of chickpea (Cicer arietinum) and its association with field emergence

Abstract: Aim: Methodology:Results: Interpretation:Pigmented (desi) and non pigmented (kabuli) cultivars of chickpea are known to differ in seed vigour. Therefore, the main objective of the study was to understand the mechanisms for such vigour differences and to identify the important seed coat and seed related vigour traits that makes the coloured desi seeds more vigorous then unpigmented kabuli seeds.Twenty two chickpea genotypes differing in seed coat colour were included in the experiment. Field emergence and elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…The priming phase contributes to the membrane repair system, by improving membrane stability, as the primed seed has a lower electrical conductivity level [ 80 ]. Related findings were obtained from sorghum seeds primed with PEG 6000 [ 4 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…The priming phase contributes to the membrane repair system, by improving membrane stability, as the primed seed has a lower electrical conductivity level [ 80 ]. Related findings were obtained from sorghum seeds primed with PEG 6000 [ 4 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Testa color is one of the main contributing factors of imbibition rate in a variety of crop plants, including soybean, rapeseed, wheat, and chickpea [ 11 , 16 , 35 , 36 ]. Indeed, as in the present study, previous studies have reported that the imbibition rates of black-seeded accessions are higher than those of yellow-seeded accessions [ 26–28 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exact point of initial entry of water to seed during imbibition is controversial. However, the hilar–micropyle region is reported to be an initial point of entry for water in legume seeds (Chen et al., 2019; Lamichaney et al., 2017). The hilar–micropyle region is covered by the funiculus and when the seed matures, it detaches itself from the funiculus, exposing the hilar–micropyle region.…”
Section: Preliminary Investigations On Role Of Intact Funiculus On Rate Of Water Imbibitionmentioning
confidence: 99%